Answer:
no solution
Step-by-step explanation:
heres why:
Let's solve your equation step-by-step.
4x−9(x+1)=20−5x
Step 1: Simplify both sides of the equation.
4x−9(x+1)=20−5x
4x+(−9)(x)+(−9)(1)=20+−5x(Distribute)
4x+−9x+−9=20+−5x
(4x+−9x)+(−9)=−5x+20(Combine Like Terms)
−5x+−9=−5x+20
−5x−9=−5x+20
Step 2: Add 5x to both sides.
−5x−9+5x=−5x+20+5x
−9=20
Step 3: Add 9 to both sides.
−9+9=20+9
0=29
so there are no solution
Answer:
10 answer is 46
Step-by-step explanation:
and 9 answer is108
44.25 - 2.25 = 42.
42/3.50 = 12
12 + 1 = 13 miles
Subtract 30, then factor the equation.
... x² = 30
... x² - 30 = 0
... (x -√30)(x +√30) = 0
By the zero product rule, the solutions are values of x that make a factor be zero.
... x - √30 = 0 . . . . the first factor is zero
... x = √30
... x + √30 = 0 . . . . the second factor is zero
... x = -√30
The solutions are . . .
... x = ±√30 . . . . . matches your 3rd choice
Wll not just this question, but whenever you need to find average, you have to:
Wait, for example let's take ur question:
1st step we will add up all the values aka heights:
5.4+6.12+7.02+4.9+6.25=29.69
And then how many values did you take???
Its, 5 values
1st value= 5.4
2nd value=6.12
aaand so on....
However, then we will have to divide the sum by no.of values
29.69÷5=5.938
Aaand this is your FINAL ANSWER
Done!!!!
Hope I helped you!!!